Social media use and alcohol consumption among students in Uganda: a cross sectional study - Edwinah Atusingwize; Maria Nilsson; Annika Egan Sjölander; John C. Ssempebwa; Nazarius Mbona Tumwesigye; David Musoke; Evelina Landstedt (Taylor & Francis Group, 2022)
Background Globally, alcohol use significantly contributes to the disease burden. Alcohol consumption in Uganda is related to several health consequences among young people, including university students. Social media is commonly used by students to share academic information and create social networks. Among young people in high-income countries, previous studies have also shown that social media use can have negative health outcomes related to alcohol use, and associated problems. To date, similar studies conducted in low- and middle-income countries are largely missing. Objective To assess the prevalence of and associations between social media use and alcohol consumption among university students in Uganda. Method This was a cross-sectional study among 996 undergraduate students at Makerere University. Data were collected using a questionnaire. Alcohol use in the previous 12 months was the dependent variable. The independent variable was social media use categorised as general use, alcohol-related use, and social media lurking/passive participation. Multinomial logistic regression was used to assess associations. Crude and adjusted odds ratios were reported. Results Nearly all students (97%) used social media and 39% reported alcohol use. Regular alcohol use was significantly associated with moderate (OR = 2.22, CI: 1.35-3.66) and high level general social media use (OR = 2.45, CI: 1.43-4.20). Regular alcohol use was also associated with alcohol-related social media (OR = 6.46, CI: 4.04-10.30), and alcohol-related lurking (OR = 4.59, CI: 2.84-7.39). Similar, although weaker associations were identified for occasional alcohol use. Conclusions Approximately four in ten students reported alcohol use in the past year, and almost all students used social media. Alcohol-related social media use was associated with occasional and regular alcohol use, with stronger associations for regular use. These findings may guide further research and present an opportunity for potential alcohol control interventions to improve health among young populations in low- and middle-income countries.